The impact of Tubaramure, a food-assisted integrated health and nutrition program in Burundi, on maternal and child anemia - Leroy, Jef L.; Olney, Deanna K.; Ruel, Marie T. (Wiley, 2015)
Tubaramure is a food‐assisted, preventive maternal and child health and nutrition (MCHN) program targeted to pregnant women and their child 0‐2 y of age (first 1000 days) in two highly food insecure provinces in Burundi. Monthly food rations include corn‐soy‐blend (CSB) and vit A‐ and D‐fortified oil. We evaluated the program's impact using a cluster randomized controlled study, where 60 villages were assigned to: T24: benefits during pregnancy up to 24 m; T18: pregnancy up to 18 m; TNFP: same as T24, but without food rations during pregnancy; and Control. We estimated the program's impact on Hb and anemia in children 0‐24 m and their mothers using double difference estimates with repeated cross‐sectional data at baseline (BL) and 2 y later (EL). We used mixed methods to document pathways of impact.Mean Hb was significantly lower at EL compared to BL in children (0.8 g/dL) and their mothers (0.7 g/dL), but the program had a significant protective effect. Compared to control, Hb in beneficiary children dropped 0.3‐0.5 g/dL less; in mothers 0‐3 m post‐partum, anemia increased 24‐39 pp less. Impact pathway analyses suggest that impacts were achieved through positive changes among children in dietary diversity, intake of Fe‐rich foods, bednet use, and lower morbidity; among mothers, bednet use appears to be part of the pathway. Differences between treatment groups will be discussed. This theory‐based impact evaluation demonstrated the effectiveness of a preventive food assisted MCHN program on children's HB and maternal anemia and highlighted the contribution of different program inputs in achieving this impact.Funded by USAID's Food and Nutrition Technical Assistance Project & CGIAR Research Program on Agriculture for Nutrition and Health (A4NH), led by IFPRI.